Transplantation of gonads: history and current situation. - Faggioni, Maurizio P. (Medicina e Morale, 1998)
The article deals with the subject of transplantation of gonads from the first attempts at the end of the nineteenth century up to today's developments, taking into consideration both the biomedical and the ethical aspects. Two possible situations are studied, the transplantation which aims to restore a deficient hormonogenesis and the transplantation which aims to restore fertility, with the aim of going back to the anthropological root of the problems. The first kind of transplantion, which in principle is lawful, nonetheless raises delicate problems concerning the possible repercussions regarding the personality of the person who undergoes the transplantation. The second kind of transplantation does not only appear to be a sophisticated variant of heterologous fertilization, but also determines a violation of personal space through the insertion of extraneous genetic information that can be transmitted to one's children. Finally, in the same perspective, the much discussed questions of the transplantation of gonadic tissue from aborted fetuses and corpses are studied, and its psychological and ethical impracticability is shown.